Relationship Between Knowledge About Gastritis And Compliance With Drug Use In Gastritis Patients At Sigumpar Community Health Center - Yanti, Fitri; Hepni Hepni; Faisal Yusuf; Opelina Simanjuntak (CV. AFDIFAL MAJU BERKAH, 2025)
Gastritis is a health disorder of the digestive tract that is experienced by many people and is a disease that is often encountered in clinics based on its clinical symptoms. Gastritis is usually called an ulcer disease, which is inflammation of the gastric mucosa due to irritation and infection, where the stomach can be damaged by the squeezing process if it occurs continuously.The aim of this study was to determine the relationship between patient knowledge about gastritis and compliance with the use of gastritis medication at the Sigumpar Community Health Center. This research method is Cross Sectional, a study used to correlate two variables. The sample in this study consisted of 36 patients with 20 patients with acute gastritis and 16 patients with chronic gastritis. Data collection uses a non-probability sampling technique, namely purposive sampling. The data analysis technique used is the Spearman test.This research states that patient knowledge about gastritis has a good level of knowledge of 80.56% with the level of compliance with the use of gastritis medication stating that 55.5% has moderate compliance. Based on the results of the Spearman test, it shows that the results. Sig value. (2-tailed) is 0.896 > 0.05, so it can be concluded that there is no significant correlation between patient knowledge about gastritis and compliance with medication use. This research is expected to increase knowledge about gastritis and compliance with medication use.